A study of prevalence and antimicrobial resistance and pathogenic activity of bacteria in the air of certain areas of Dhaka city - Ashraf, Anika; Faria, Tasnuva (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.